If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3Y + -5) = -8 Reorder the terms: -2(-5 + 3Y) = -8 (-5 * -2 + 3Y * -2) = -8 (10 + -6Y) = -8 Solving 10 + -6Y = -8 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -6Y = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -6Y = -8 + -10 -6Y = -8 + -10 Combine like terms: -8 + -10 = -18 -6Y = -18 Divide each side by '-6'. Y = 3 Simplifying Y = 3
| 2x+73=8x-11 | | -18=2a | | 6m^2+9m-6=0 | | 13x-6=9x+14 | | 3x+10+40= | | 10x/y | | -3(-7+m)= | | 3x-5=137 | | 17x=5y+1 | | -4a^2-45a-50=0 | | x+48=x | | 8v+13=3v+18 | | 3x+40+10=180 | | 6(2x+4)=3(8+4x) | | x^-3/2=0 | | 6x-5y+3=-27 | | 9cot^2x+1=4 | | X^3-4x^2-14x-60=0 | | 3x+10+40=360 | | 9=3p+6 | | 8b-13b= | | 9cot^2x=4 | | x+4+2x=137 | | 11s+12t=93 | | P=275/12i1714 | | 7w+4=5w-10 | | 6(2Y+2)-9=3 | | 1-7x=6x-129 | | 2(T-2)+9=-9 | | 5(3x-1)=-10x+20 | | 6/(2/3) | | 9(5n+4)= |